2018
DOI: 10.1002/star.201800098
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acid Treatment and Freeze-Thaw Cycle on Textural Properties and Microstructure of Cooked Aged Rice

Abstract: This research aims to improve frozen cooked aged rice's textural properties using lime juice, citric acid, and ascorbic acid solutions. Aged (12 months) rice is cooked and freeze‐thawed up to 3 cycles. Cooked fresh rice (0.7 months) is used as a reference. Addition of acid significantly decreases hardness but significantly increases stickiness for freeze‐thawed, cooked, aged rice (p ≤ 0.05). Scanning electron micrographs show a rough surface on cooked rice after repeated freeze‐thaw cycles, especially for cook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Notably, it has been suggested that ice crystal formation during freezing and storage is a critical factor that determines the quality of frozen cooked rice. In addition, many researchers have reported that freezing rate was directly related to ice crystal morphology and physical properties related to textural characteristics, as it affects the time required to pass through the maximum ice crystal formation zone during freezing (Kono, Kawamura, Yamagami, Araki, & Sagara, ; Kono, Tobari, Araki, & Sagara, ; Trithavisup & Charoenrein, ; Ye et al., ; Yu, Ma, Liu, Menager, & Sun, ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, it has been suggested that ice crystal formation during freezing and storage is a critical factor that determines the quality of frozen cooked rice. In addition, many researchers have reported that freezing rate was directly related to ice crystal morphology and physical properties related to textural characteristics, as it affects the time required to pass through the maximum ice crystal formation zone during freezing (Kono, Kawamura, Yamagami, Araki, & Sagara, ; Kono, Tobari, Araki, & Sagara, ; Trithavisup & Charoenrein, ; Ye et al., ; Yu, Ma, Liu, Menager, & Sun, ).…”
Section: Introductionmentioning
confidence: 99%